Critiques on the Tribunals and The Hague Court - Pathak, Bishnu (Advances in Social Sciences Research Journal, 2020)
This critique is a review of heinous crimes. It assesses to connect with perpetrators, victims, people and institutions and change professed through the works of the Tribunals and The Hague Court and share the feeling with the concerned ones. The objectives of the paper are three-fold: (1) to study the situations of the investigation, prosecution and punishment on accountability; (2) to analyze the preference for justice: victors’ justice or victims’ justice; and (3) to access the critiques on violations of human rights and humanitarian law beyond the borders. Experiences on Transitional Justice, Human Security, and Human Rights among others feel touched, inspired and motivated to the author for this pioneer paper. This state-of-the-art paper is examined based on archival research, exchanging and sharing way forward with over 100 international publications and lessons-learned centric theoretical approach comprising snow-ball techniques. The study theorizes: (1) Retributive Justice Theory: Punishment is justified as perpetrator deserves for penalty, equivalent vengeance; (2) Utilitarian Justice Theory: Punishment is justified to mid-and-junior level perpetrators scooting-free to the top-most policymakers including Emperor Hirohito. Allied powers believed that Hirohito can only fight against the communism; (3) Denunciation Justice Theory: Punishment is justified by pressure of society that sends a clear message: offence is a heinous crime and sentencing a perpetrator is logically just; (4) Restorative Justice Theory: Punishment is justified as crimes of perpetrators hurt everyone and justice repairs the damage satisfying through accountability, reparation, rehabilitation and reconciliation; and (5) Transnational Justice Theory: Punishment is justified to operate outside a nation territory that penalizes the perpetrators as a crime of international concern. The Nuremberg and Tokyo Tribunals had virtually been victor’s justice with self-righteous fraud and lynching bodies. The Tokyo Tribunal never talks about bombings at Chinese cities. The U.S. and its axis powers discourage future aggressions accepting victor’s justice. The UN failed to restore peace and security. Cronyism was/is widespread. All Tribunals seemed pseudo justice bodies. People criticize these for being one-sided, inefficient, ineffectiveness, politicized, lengthy, very costly and unfair bodies. The U.S. and its satellite nations control both Tribunals and The Hague Court providing funds, instruments and staff. The Hague Court is a highly debated body with many flaws, targeting mostly poor and opponent African countries. Most grave crimes committed go unpunished. Thus, justice delivery appears as a sword in a judge's toupee. If The Hague Court is continuously influenced by powerful non-signatories of Statute, the relevance of its functions are hopeless. Justice becomes elusive for the innocent, weak and poor ones.